6‐Acetoxy Cyperene, a Patchoulane‐type Sesquiterpene Isolated from Cyperus rotundus Rhizomes Induces Caspase‐dependent Apoptosis in Human Ovarian Cancer Cells. (10th June 2015) - Ahn, Ji‐Hye; Lee, Tae‐won; Kim, Ki‐Hee; Byun, Hoyong; Ryu, Byeol; Lee, Kyung‐Tae; Jang, Dae Sik; Choi, Jung‐Hye
<x xml:space="preserve">Abstract</x> Cyperus rotundus (Cyperaceae) has been widely used in traditional medicine for the treatment of various diseases, including cancer. Although an anti‐tumour effect has been suggested for C. rotundus, the anti‐tumour effects and underlying molecular mechanisms of its bioactive compounds are poorly understood. The n‐hexane fraction of an ethanol extract of C. rotundus rhizomes was found to inhibit cell growth in ovarian cancer (A2780, SKOV3 and OVCAR3) and endometrial cancer (Hec1A and Ishikawa) cells. Among the thirteen sesquiterpenes isolated from the n‐hexane fraction, some patchoulane‐type compounds, but not eudesmane‐type compounds, showed moderate cytotoxic activity in human ovarian cancer cells. In particular, the patchoulane sesquiterpene 6‐acetoxy cyperene had the most potent cytotoxicity. In this regard, propidium iodide/Annexin V staining and terminal deoxynucleotidyl transferase dUTP (deoxynucleotide triphosphate) nick end labeling assay were performed to study cell cycle progression and apoptosis. 6‐acetoxy cyperene induced apoptosis, as shown by the accumulation of sub‐G1 and apoptotic cells. Furthermore, treatment with 6‐acetoxy cyperene stimulated the activation of caspase‐3, caspase‐8 and caspase‐9 and poly(ADP‐ribose)polymerase in a dose‐dependent manner. Pretreatment with caspase inhibitors neutralized the pro‐apoptotic activity of 6‐acetoxy cyperene. Taken together, these data suggest that 6‐acetoxy cyperene, a patchoulane‐type sesquiterpene isolated from C. rotundus rhizomes, is an anti‐tumour compound that causes caspase‐dependent apoptosis in ovarian cancer cells. Copyright © 2015 John Wiley & Sons, Ltd.